Somatostatin receptor subtype 2 (sst2) is a potential prognostic marker and a therapeutic target in medulloblastoma - Remke, Marc; Hering, Esther; Gerber, Nicolas U.; Kool, Marcel; Sturm, Dominik; Rickert, Christian H.; Gerß, Joachim; Schulz, Stefan; Hielscher, Thomas; Hasselblatt, Martin; Jeibmann, Astrid; Hans, Volkmar; et al. (Child's nervous system, 2013)
Neuroectodermal tumors in general demonstrate high and dense expression of the somatostatin receptor subtype 2 (sst2). It controls proliferation of both normal and neoplastic cells. sst2 has thus been suggested as a therapeutic target and prognostic marker for certain malignancies.